Reconfiguring Gender and Family in Musical Cinema: A Comparative Analysis of Mamma Mia! (2008) and Contemporary Popular Films - M Afifulloh; Azra Khashia Nafisa; Chalisa Azzahra; Naomi Kania Dealova (Journal of General Education and Humanities, 2026)
This study addresses the limited comparative analysis in previous research on musical films, which often focuses on single-text interpretations of gender, identity, and family representations. Accordingly, the objective of this research is to examine how Mamma Mia! constructs these meanings within the broader context of contemporary musical cinema by comparing it with The Sound of Music, Frozen, and Little Women. This study employs a qualitative research method using comparative textual analysis, drawing on representation theory, feminist media theory, and the sociology of family. The findings demonstrate that Mamma Mia! not only reflects evolving gender norms but also actively redefines family structures through post-patriarchal representations, emotional autonomy, and the concept of chosen family. In contrast to earlier cinematic traditions, the film indicates a shift toward postfeminist sensibilities characterized by agency, fluid identity, and affective kinship. This study contributes to media studies by emphasizing that musical films function as ideological spaces where social meanings are negotiated and transformed.